Insulin hexamer dissociation dynamics revealed by photoinduced T-jumps and time-resolved X-ray solution scattering. Issue 7 (1st June 2018) - Rimmerman, Dolev; Leshchev, Denis; Hsu, Darren J.; Hong, Jiyun; Abraham, Baxter; Kosheleva, Irina; Henning, Robert; Chen, Lin X.
Abstract : The structural dynamics of insulin hexamer dissociation were studied by the photoinduced temperature jump technique and monitored by time-resolved X-ray scattering. Abstract : The structural dynamics of insulin hexamer dissociation were studied by the photoinduced temperature jump technique and monitored by time-resolved X-ray scattering. The process of hexamer dissociation was found to involve several transient intermediates, including an expanded hexamer and an unstable tetramer. Our findings provide insights into the mechanisms of protien–protein association.